Electrochemical and in situ Spectroelectrochemical Properties of Phthalocyanines Bearing N-Benzyl-4-Phenyloxyacetamide Moieties - ÖZKAYA, ALİ RIZA (WALTER DE GRUYTER GMBH, 2011)
The general redox behaviour of phthalocyanines bearing N-benzyl-4-phenyloxyacetamide moieties (H2Pc, ZnPc, NiPc, CuPc, and CoPc) has been identified by cyclic voltammetry and differential pulse voltammetry on Pt in dimethylsulfoxide/tetrabutylammonium perchlorate. These measurements showed that the complexes indicate subsequent one-electron reduction and oxidation processes. Although the voltammetric measurements implied the association of the redox processes of some complexes with aggregation phenomenon, the complete evaluation of the aggregation effects by only these measurements was not possible. In situ UV-Vis spectroelectrochemical measurements enabled us to assign the ligand- and metal-based redox processes, and identify if the aggregation affects these processes. These measurements suggested that the redox processes of H2Pc, NiPc, and CuPc are coupled by aggregation phenomenon, while those of ZnPc and especially CoPc are not, probably due to the difference in their axial coordinating properties.
Keywords: Phthalocyanines; Electrochemistry; Spectroelectrochemistry; Aggregation; METAL-FREE; PHOTOPHYSICAL PROPERTIES; AGGREGATION PROPERTIES; COPPER PHTHALOCYANINE; COMPLEXES; COBALT; ACID; METALLOPHTHALOCYANINES; TETRASULFONATE; SUBSTITUENTS